Manuscript, Print and the Market for Music in Early Modern Europe - Iain Fenlon (De Musica Disserenda, 2015)
The shifting tensions between two major features of the dissemination of music in the early modern era – between manuscript and printed transmission on the one hand, and between “centre” and “periphery” on the other – are explored in this paper via the example of the dissemination of the motet Aspice Domine by Jacquet of Mantua. Central to the dynamics of both is the evolution of an expanding market for printed books of music, a process stimulated by technological innovation as well as by significant changes in societal attitudes towards the art of music itself – changes that were themselves promoted through the medium of print.